Mycobacterium bovis -induced Human Tuberculosis in Central India - Ajay Vir Singh; Devendra Singh Chauhan (Springer, 2018)
Tuberculosis (TB) caused by Mycobacterium bovis (M. bovis) in animals (bovine TB) and humans (zoonotic TB) remains an important economic and zoonotic problem in most of the livestock-producing countries of the world. Humans mainly acquire M. bovis infection through close contact with infected animals or consumption of contaminated animal products. India has a high number (>512 million) of livestock animals and with >1.3 billion humans ranked as the second most populated country in the world. Approximately 68.0% of the Indian workforce relies on farming to secure their livelihood and is in close contact with domestic animals. Despite the reported high prevalence of bovine TB in domestic animals, information on the epidemiologic characteristics and public health aspects of M. bovis infection in humans remain largely unknown in India.